Total synthesis of Reniochalistatin E and synthetic efforts towards Lagunamide C - Fatino, Anthony James (Kansas State University, 2021)
Natural products (NPs) are compounds isolated from any living organisms and continue to be a rich source of medicines, especially chemotherapeutics. In order to develop new anticancer compounds, this work aimed to synthesize two NPs, reniochalistatin E and lagunamide C, shown below. Reniochalistatin E is a cyclic octapeptide with anticancer activity in a variety of cancer cell lines; including, myeloma (RPMI-8226: IC₅₀ = 4.9 [mu]M), gastric (MGC-803: IC₅₀ = 9.7 [mu]M), and cervical (HeLa: IC₅₀ = 24.4 [mu]M). To this end, the first total synthesis of reniochalistatin E has been completed in 15 steps with an overall 5% yield. Analog synthesis and biological testing identified the tryptophan amino acid (shown in red) as a site for drug conjugation. Future work will harness the synthetic route to generate a cysteine analog in order to conjugate the FDA approved chemotherapeutic, 6-thiopurine (6TP), though a disulfide linkage. Lagunamide C is a cyclic depsipeptide with potent cytotoxic activity in a number of cell lines including lymphoma (P388: IC₅₀ = 24.4 nM), lung (A549: IC₅₀ = 2.4 nM), colon (PC3: IC₅₀ = 2.1 nM), and ovarian (SK-OV3: IC₅₀ = 4.5 nM). This work highlights a module-based approach to access the diastereoselective polyketide fragment (shown in blue). Key stereogenic steps include an aldol reaction with an N-acetylated Crimmins auxiliary, an asymmetric cyclopropanation with tandem ring-opening, and an iridium catalyzed allylation. Future work will look to complete the first total synthesis of lagunamide C and identify the importance of each subunit of the NP through SAR and analog synthesis.
Keywords: Natural products; Organic synthesis